Pengembangan Petunjuk Praktikum Pencemaran Air Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar Siswa SMP - Siti Fitrotul Mufidah; Tabitha Sri Hartati Wulandari (Universitas Sebelas Maret, 2018)
Teaching materials that support practicum activities are practical guides. The result of observation at SMPN 1 Brondong shows that the practicum guide used has deficiencies in terms of component completeness. This study aims to: 1) produce qualified practical intructions water pollution based on guided inquiry (valid, practical and effective); 2) to describe the validity, practicality and effectiveness of guided inquiry guide. This research is a development research using Four-D development model, however, in this research and development, activities are carried out only until the development stage. The results of research and development show: 1) produce qualified practical intructions water pollution based on guided inquiry developed based on guided inquiry activity; 2) the validity test results from the categorized experts of the category